Consumer value dimensions of rural tourism in Hungary - Kulcsár, Noémi (Hungarian Geographical Bulletin, 2015)
Considering the geographical and historical characteristics of Hungary, rural tourism could be one of the key tourism products since the country misses extraordinary natural attractions, seaside or high mountains. Hungary has always been an agricultural country and it is rich in cultural landscape with traditional small villages and rural hospitality. As in Hungary theoretical research on consumer value factors in rural tourism is completely missing the primary aim of our investigation was to conduct a niche survey in rural tourism, which can contribute to the bett er understanding of the demand side of the market and crystallise the factors with value to tourists. The aim of the pilot study based on qualitative research is to identify and measure consumer value dimensions. In our qualitative research first we completed indicators identified by secondary sources with further indicators, as the result of a small sample consumer survey, then we have refined the created list of indicators on the basis of expert opinions. As the next step of the research we have conducted a quantitative questionnaire-based survey, by which the aim was to identify, interpret and analyse the motivations of rural tourist and the indicator-based consumer value with its major dimensions. In this paper we discuss only the latter phase of our research in more detail. The basis of success of rural tourism in Hungary can be the identification of tourists’ motivations, attitudes, as well as factors that carry value for them, since it may reveal useful information both scientifically and practically.